2020
DOI: 10.1111/imb.12671
|View full text |Cite
|
Sign up to set email alerts
|

Caste‐specific gene expression underlying the differential adult brain development in the honeybee Apis mellifera

Abstract: Apis mellifera adult workers feature more developed key brain regions than queens, which allows them to cope with the broad range of duties they need to perform in a colony. However, at the end of larval development, the brain of queens is largely more developed than that of workers. Major morphogenetic changes take place after metamorphosis that shift caste‐specific brain development. Here, we tested the hypothesis that this phenomenon is hormonally governed and involves differential gene expression. Our mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We also showed that these genes are indeed differentially expressed during key (Hartfelder and Engels, 1998), these hormones are unlikely to regulate the expression of hexamerin genes in the brain, as suggested for other honeybee tissues and insect species (Martins et al, 2010;Webb and Riddiford, 1988). Since hexamerin genes are typically considered to be nutrient- responsive, one can speculate on the occurrence of a wave of molecular building blocks being released from the fat body to the haemolymph and recaptured from there by diverse tissues, including that of the brain, which are going through striking morphogenetic changes (Paula Junior et al, 2021). This would induce the expression of hexamerin genes in paralleled waves thus explaining the observed transcription profiles.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We also showed that these genes are indeed differentially expressed during key (Hartfelder and Engels, 1998), these hormones are unlikely to regulate the expression of hexamerin genes in the brain, as suggested for other honeybee tissues and insect species (Martins et al, 2010;Webb and Riddiford, 1988). Since hexamerin genes are typically considered to be nutrient- responsive, one can speculate on the occurrence of a wave of molecular building blocks being released from the fat body to the haemolymph and recaptured from there by diverse tissues, including that of the brain, which are going through striking morphogenetic changes (Paula Junior et al, 2021). This would induce the expression of hexamerin genes in paralleled waves thus explaining the observed transcription profiles.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, at least one of the hexamerin genes, hex70b, whose protein seems to represent the typical storage hexamerin (Martins and Bitondi, 2012), has been suggested to participate in the differential caste development of honeybees, likely through inhibiting the morphogenetic activity of JH, like in R. flavipes (Zhou et al, 2006(Zhou et al, , 2007. HEX110 and HEX70a have recently gained more attention since reports of our group demonstrated not only their non-canonical tissue expression (Martins et al, 2011;Martins and Bitondi, 2016;Paula Junior et al, 2021;Vieira et al, 2021), but also suggested they Lines highlighted in grey: used in the quantitative PCR assays. Time (in hours) after larva eclosion.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic mechanisms acting at different developmental stages are responsible for differential brain development in A. mellifera workers and queens [131]. tum, mnb, Tor, and insulin receptor 1 (InR-1) genes are expressed at greater rates in workers than queens during development.…”
Section: Neural Tissue and Functionalitymentioning
confidence: 99%
“…tum, mnb, Tor, and insulin receptor 1 (InR-1) genes are expressed at greater rates in workers than queens during development. In contrast, insulin-like growth factor (IGF, see Table 1) is expressed more in queens during the same phase [131]. Notably, tum and mnb have known neurogenic function [132,133], while RNAi knockdown of Tor has been shown to induce a worker phenotype by reducing JH levels in queen-destined larvae [134].…”
Section: Neural Tissue and Functionalitymentioning
confidence: 99%
See 1 more Smart Citation